Copper-Catalyzed Oxidative α-Ketoacylations of Sulfoximines with Aryl Methyl Ketones and Dioxygen as Terminal Oxidant - Cheng, Hanchao; Bolm, Carsten (Synlett, 2016)
An efficient copper-catalyzed C−H/N−H bond functionalization for the synthesis of α-keto-N-acyl sulfoximines from aryl methyl ketones and NH-sulfoximines with molecular oxygen as terminal oxidant has been developed.
Keywords: sulfoximine; ketone; dioxygen; oxidative coupling; α-ketoacylation